2022
DOI: 10.1038/s41531-022-00352-5
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin ameliorates Parkinson’s disease via regulating microglia polarization in a RORα‐dependent pathway

Abstract: An important pathophysiological component of Parkinson’s Disease (PD) is circadian rhythm disorder, closely related to a decrease in circulated melatonin (MLT) level. It has been reported recently that retinoic acid-associated orphan nuclear receptor (RORα), for the potentiallyendogenous ligand MLT, plays an important role in various diseases. However, the function of RORα in the pathogenesis of neurodegenerative diseases remains much unclear. Here, we showed in a cellular PD model that RORα expression was dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…63 Li et al discovered that MEL promoted MG polarization to M2 through STAT signaling pathway, therefore inhibiting neuroinflammation in parkinsonism-related symptoms. 64 In our study, we found that MEL influenced MG polarization probably through RhoA/ROCK signaling pathway. When neurons are injured, Rho is activated and induces the atrophy of growth cone and axon regeneration disorder.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…63 Li et al discovered that MEL promoted MG polarization to M2 through STAT signaling pathway, therefore inhibiting neuroinflammation in parkinsonism-related symptoms. 64 In our study, we found that MEL influenced MG polarization probably through RhoA/ROCK signaling pathway. When neurons are injured, Rho is activated and induces the atrophy of growth cone and axon regeneration disorder.…”
Section: Discussionsupporting
confidence: 49%
“…Besides, Zhou et al found that MEL shifted M1 MG toward M2 through MT1/JAK2/STAT3/telomerase pathway and ameliorated periventricular white matter injury in rats 63 . Li et al discovered that MEL promoted MG polarization to M2 through STAT signaling pathway, therefore inhibiting neuroinflammation in parkinsonism‐related symptoms 64 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 It modulates microglial polarization and reduces neuroinflammation through its antioxidant and antistress properties. 18 Melatonin acts on G-protein-coupled receptors, mainly MT1 and MT2. 19 Altered microglial metabolism and increased neuroinflammation in PD are associated with MT1 deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin, a hormone secreted by the pineal gland, has potent neuroprotective effects in PD 17 . It modulates microglial polarization and reduces neuroinflammation through its antioxidant and antistress properties 18 . Melatonin acts on G‐protein‐coupled receptors, mainly MT1 and MT2 19 .…”
Section: Introductionmentioning
confidence: 99%